Water Purification Using Prototype of Constructed Wetland and Its Use in Aquaponic at Cinangsi Village, Cianjur - Taufik Taufikurahman; Endra Susila; Asih Suryati; Julita Fitrianti; Gilbert Hanshi; Difa Salmadhia (Center for Rural Areas Empowerment (P2D), Institut Teknologi Bandung, 2024)
In several rural areas, the lack of clean water availability forced them to use polluted water to accommodate their daily needs. For example, in Cinangsi Village, Cianjur District, West Java, the local communities is forced to use contaminated river water for their daily use. The river water is contaminated by the disposal of fish farming waste directly into the river. To solve this problem, constructed wetland combined with aquaponic system is implemented. The constructed wetland can provide better water quality, while the aquaponic system can create a sustainable cultivation system that can be profitable for the local communities. In this paper we describe a prototype of the constructed wetland combined with aquaponic system that we have built in Cinangsi Village and the results in solving the clean water shortages problem, especially in Cinangsi Village.